"Don't keep mum": critical approaches to the narratives of women intelligence professionals. Issue 4 (7th June 2021) - Shahan, Jess
ABSTRACT: Drawing upon a rise of women's publicly shared narratives in the UK and US in the previous two decades, this article aims to challenge traditional perceptions of intelligence employment, finding that gender is an influential factor in career experiences and trajectories. We can gain unique insights into organizational practices and cultures by analyzing the ways in which women speak about their careers. Narratives are valuable but underutilized sources in intelligence studies. In incorporating critical approaches to women's narratives, the intention is to move beyond the 'finding' of women in intelligence history to reveal a more nuanced understanding of intelligence work.